A quadripartite model of passion for marijuana use: associations with consumption, consequences, craving, and satisfaction with life. (2nd January 2021) - Dolan, Sean; Arterberry, Brooke; Davis, Alan
Abstract: Background: Identifying factors that can be targeted in intervention/prevention programs aimed at reducing marijuana (MJ)-related consequences is of critical concern due to the changing legislative landscape of MJ. The dualistic model of passion for MJ has indicated that two factors, obsessive passion (OP) and harmonious passion (HP), have unique effects associated with MJ use outcomes. New research suggests that a quadripartite approach could provide a more nuanced method to interpret risk and protective factors associated with MJ use. Therefore, we used moderation to investigate the associations among OP, HP, and MJ use outcomes. Method: A community sample of frequent MJ users was recruited using internet-based advertisements and completed web-based surveys ( n = 161; M age = 27.3, SD = 8.9; Male = 87%; White/Caucasian = 86%; M past 30-day MJ use = 22.3, SD = 9.9). HP was tested as the moderator between OP, and MJ-related outcomes and conditional effects (±1 SD ) were examined when interaction effects were significant. Results: Only main effects for OP had a relation to quantity/frequency of MJ use and MJ intoxication, while main effects for OP and HP were associated with reduction attempts. Interaction effects were significant for MJ consequences, craving, and life satisfaction. Neither OP nor HP were significantly associated with substance use outcomes. Conclusions: Findings demonstrate that Pure OP and Mixed Passion are associated with greater risk. Mixed Passion may be a precursor to Pure OP and experiencing MJ-related consequences. Furthermore, Mixed Passion and Pure OP may be important targets for intervention/prevention programs designed to reduce negative outcomes.